PENGARUH CITRA MEREK, KUALITAS PRODUK DAN PERSEPSI HARGA TERHADAP KEPUTUSAN PEMBELIAN HELM MEREK INK (Studi Pemakai Helm Merek INK pada Mahasiswa Fakultas Ekonomika dan Bisnis Unisbank Semarang) - Putri Widiastuti, 14.05.51.0137; Tjahjaningsih, Endang (Students' Journal of Economic and Management, 2018)
The purpose of this study is to describe and analyze the influence of brand image, product quality and price perception of purchasing decisions in the use of INK helmet. In this study the independent variables that influence purchasing decisions are limited to brand image variables, product quality and price perceptions. Population in this research is student of Faculty of Economics and Business at Unisbank Semarang. And selected as many as 100 respondents are used as a sample. Data testing techniques used include validity test with factor analysis, reliability test with cronbach alpha, multiple linear regression analysis and significance test of coefficient of determination to prove the truth of the hypothesis.Test results obtained that there is significant effect of brand image variables on purchasing decisions. There is a significant effect of product quality variables on purchasing decisions. There is significant influence of price perception variable to purchase decision. Keywords: Brand Image, Product Quality, Price Perception, And Purchasing Decisions